2011
DOI: 10.1186/1471-2334-11-302
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and cost of herpes zoster and postherpetic neuralgia among patients treated in primary care centres in the valencian community of Spain

Abstract: BackgroundData on the epidemiology and costs related to herpes zoster (HZ) and postherpetic neuralgia (PHN) in Spain are scarce; therefore, studies are needed to evaluate the epidemiological and economic impact of HZ and its most common complication, PHN. The present study aimed to estimate the clinical and economic burden of HZ and PHN in Valencia (Spain).MethodsWe prospectively analyzed the burden of HZ and PHN and their attributable costs in patients from 25 general practices in the Autonomous Community of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
4
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 37 publications
6
58
4
3
Order By: Relevance
“…A recent study has shown no significant differences in the incidence of HZ between European countries. 24 In addition, studies in Spain (Navarre, 19 Valencia, [14][15][16] and Madrid 18 ) based on administrative data from primary healthcare show very similar results (overall incidence in all age groups of about 4 per 1000 inhabitants, although the Valencian study 14,15 did not include subjects aged <14 y). The study by Yawn et al, 7 one of the most comprehensive epidemiological studies of HZ, found similar incidence rates to those observed in Spain, as did other studies performed in Europe, [25][26][27][28][29] Israel, 30 and the United States.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…A recent study has shown no significant differences in the incidence of HZ between European countries. 24 In addition, studies in Spain (Navarre, 19 Valencia, [14][15][16] and Madrid 18 ) based on administrative data from primary healthcare show very similar results (overall incidence in all age groups of about 4 per 1000 inhabitants, although the Valencian study 14,15 did not include subjects aged <14 y). The study by Yawn et al, 7 one of the most comprehensive epidemiological studies of HZ, found similar incidence rates to those observed in Spain, as did other studies performed in Europe, [25][26][27][28][29] Israel, 30 and the United States.…”
Section: Discussionmentioning
confidence: 88%
“…In Spain, incidence studies of HZ have been published based on data obtained from public primary healthcare centers in Valencia, [14][15][16] Madrid 17,18 and Navarre. 19 In Navarre, which has an excellent public health system, the proportion of patients seen by private family physicians and dermatologists is very low.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zoster may occur less frequently in tropical areas, because of later acquisition of primary infection 25 . Most of the study neither found any seasonal variation 9,16,17 nor any epidemic 9 .…”
Section: Discussionmentioning
confidence: 76%
“…It is prevalent worldwide, occurs more sporadically than does primary infection (varicella) 6 . Age is one of the strong risk factor for HZ [9][10][11][12][13] . It is uncommon in childhood and the incidence increases with age 5,10,17 .…”
Section: Discussionmentioning
confidence: 99%